Optimization studies of oil palm empty fruit bunch liquefaction for carbon cryogel production as catalyst in levulinic acid esterification - Zainol, M. M. (Penerbit UTM Press, 2018)
Liquefaction of oil palm empty fruit bunch (EFB) using 1-butyl-3-methylimidazolium chloride was investigated in this study. The experiments were designed based on central composite by response surface methodology (RSM). The optimum conditions for the predicted liquefied EFB yield of 80.97 wt% was obtained at the temperature of 151.9 °C, a reaction time of 112.78 min and a ratio (Ionic liquid to EFB) of 4.27. The Regression coefficient (R2) for the model was 0.90 indicating a high correlation between observed and predicted values. The liquefied EFB mixture was used in the preparation of carbon cryogel via a sol-gel poly-condensation reaction and calcination process. The presence of sulfuric acid during the gel synthesis promoted an active site on the gel linkage and surface. The carbon cryogel prepared was tested as catalyst in an esterification reaction. The conversion of levulinic acid and yield of ethyl levulinate were reported as 58.7% ansd 57.2 mol%, respectively.